Non-calcined alumina-silica brick for hot blast furnace or blast furnace shaft part and manufacturing method of non-calcined alumina-silica brick for hot blast furnace or blast furnace shaft part
A non-sintered alumina silica brick with specific composition and manufacturing process is developed to address the embrittlement issue caused by hydrogen in blast furnaces, achieving high hydrogen gas resistance and maintaining mechanical strength.
Patent Information
- Application Number
- JP2023166107
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-08
AI Technical Summary
The use of hydrogen as a reducing agent in blast furnaces can cause embrittlement in alumina silica bricks due to the formation of SiO gas at high temperatures, leading to a need for bricks with enhanced hydrogen gas resistance.
A non-sintered alumina silica brick with specific composition ranges (30-90% Al2O3, 10-65% SiO2, 0.5-4% P2O5) and a manufacturing method involving kneading alumina, silica particles, and an aqueous phosphate solution, followed by drying at 250-500°C, is developed to achieve high hydrogen gas resistance.
The developed non-sintered alumina silica brick exhibits high hydrogen gas resistance, maintaining mechanical strength and heat-resistant spalling properties even when exposed to high-temperature hydrogen, thus preventing embrittlement.
Smart Images

Figure 2025056560000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an unburned alumina-silica brick for use in a hot stove or blast furnace shaft, and a method for producing an unburned alumina-silica brick for use in a hot stove or blast furnace shaft. [Background technology]
[0002] Traditionally, coke has been used as a reducing agent for iron ore in the steelmaking process. In order to reduce CO2 emissions, efforts have begun to replace part of the coke with hydrogen as a reducing agent for iron ore. Clay-bonded fired alumina-silica bricks are used in hot stoves. Clay-bonded fired alumina-silica bricks are disclosed in Patent Document 1. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2017-65956 A Summary of the Invention [Problem to be solved by the invention]
[0004] When hydrogen is blown into a blast furnace as a reducing agent for iron ore, the atmosphere in the hot stove becomes reducing due to the presence of hydrogen. The high-temperature hydrogen reacts with the SiO2 in the bricks to produce SiO gas, which may cause the bricks to become embrittled.
[0005] Therefore, it is preferable that the bricks used in the hot stove or blast furnace shaft have high resistance to embrittlement even when they come into contact with high-temperature hydrogen (hereinafter, this is referred to as hydrogen gas resistance). In one aspect of the present disclosure, it is preferable to provide an unburned alumina-silica brick for use in a hot stove or blast furnace shaft, which has high hydrogen gas resistance, and a method for producing an unburned alumina-silica brick for use in a hot stove or blast furnace shaft. [Means for solving the problem]
[0006] One aspect of the present disclosure is an unfired alumina-silica brick for a hot stove or blast furnace shaft, containing 30% by mass or more and 90% by mass or less of Al2O3, 10% by mass or more and 65% by mass or less of SiO2, and 0.5% by mass or more and 4% by mass or less of P2O5. The unfired alumina-silica brick for a hot stove or blast furnace shaft of the present disclosure has high hydrogen gas resistance.
[0007] Another aspect of the present disclosure is an unfired alumina-silica brick for use in a hot stove or blast furnace shaft, the unfired alumina-silica brick for use in a hot stove or blast furnace shaft of the present disclosure having high hydrogen gas resistance.
[0008] Another aspect of the present disclosure is a method for producing an unfired alumina-silica brick for a hot stove or blast furnace shaft, comprising molding a mixture of alumina-containing particles, silica-containing particles, and an aqueous phosphate solution, and drying the molded product at a temperature of 250° C. or higher and 500° C. or lower.
[0009] The manufacturing method of the present disclosure can produce unfired alumina-silica bricks having high hydrogen gas resistance for use in a hot stove or blast furnace shaft. [Brief description of the drawings]
[0010] [Figure 1] FIG. 2 is an explanatory diagram illustrating the configuration of an evaluation device used to evaluate hydrogen gas resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Exemplary embodiments of the present disclosure will now be described with reference to the drawings. 1. Composition of unfired alumina-silica bricks The unburned alumina-silica brick for a hot stove or blast furnace shaft according to the present disclosure (hereinafter sometimes simply referred to as unburned alumina-silica brick) is used in a hot stove or blast furnace shaft. The hot stove includes bricks. The bricks are heated by burning exhaust gas from a blast furnace. The heated bricks heat air to generate hot air. The hot air is sent to the blast furnace.
[0012] The unfired alumina siliceous brick contains Al2O3, SiO2, and P2O5. P2O5 is included in phosphates. In the unfired alumina siliceous brick, the content of Al2O3 is, for example, 30% by mass or more and 90% by mass or less. When the content of Al2O3 is 30% by mass or more and 90% by mass or less, fire resistance and strength sufficient to withstand operation are obtained. The content of Al2O3 is more preferably 45% by mass or more and 70% by mass or less, and particularly preferably 50% by mass or more and 60% by mass or less.
[0013] The content of any component in the unfired alumina-silica brick means the mass ratio of that component to the total mass of the unfired alumina-silica brick. The content of Al2O3, SiO2 and P2O5 is measured by a method using fluorescent X-ray analysis in accordance with JIS R 2216.
[0014] In the unfired alumina-silica brick, the SiO2 content is, for example, 10% by mass or more and 65% by mass or less. When the SiO2 content is 10% by mass or more and 65% by mass or less, heat spalling resistance that can withstand operation is obtained. The SiO2 content is more preferably 25% by mass or more and 55% by mass or less, and particularly preferably 35% by mass or more and 45% by mass or less.
[0015] In the unfired alumina siliceous brick, the P2O5 content is, for example, from 0.5% by mass to 4% by mass. When the P2O5 content is from 0.5% by mass to 4% by mass, the unfired alumina siliceous brick has higher hydrogen gas resistance. The P2O5 content is more preferably from 0.7% by mass to 2% by mass, and particularly preferably from 0.9% by mass to 1.5% by mass. Examples of phosphates containing P2O5 include aluminum phosphate.
[0016] In this specification, particle size is defined as follows: "Coarse particles" are particles with a particle size of 1 mm or more and less than 5 mm; "Medium particles" are particles with a particle size of 0.074 mm or more and less than 1 mm; and "Fine powder" are particles with a particle size of less than 0.074 mm. The above particle sizes are measured using a test sieve specified in the Japanese Industrial Standard JIS Z8801-1.
[0017] The raw materials used for producing the unfired alumina siliceous bricks contain, for example, 30% to 50% by mass of coarse particles, 0% to 40% by mass of medium particles, and 10% to 40% by mass of fine powder. The mixing ratio of the coarse particles, medium particles, and fine powder in the raw materials can be appropriately adjusted. In order to set the porosity and compressive strength of the unfired alumina siliceous bricks in suitable ranges, it is preferable that the raw materials contain approximately 40% by mass of coarse particles, 10% to 30% by mass of medium particles, and 20% to 30% by mass of fine powder.
[0018] The unfired alumina-silica brick includes, for example, a matrix portion and aggregate. Examples of the aggregate include alumina-silica particles, alumina particles, and silica particles. Examples of the alumina-silica particles constituting the aggregate include clay, chamotte particles, andalusite particles, and mullite particles.
[0019] Examples of the aluminous particles constituting the aggregate include aluminous shale, bauxite, brown alumina, fused alumina, calcined alumina, etc. Examples of the siliceous particles constituting the aggregate include silica stone, etc.
[0020] The matrix portion is, for example, composed of fine powder. The particle size of the fine powder is, for example, 0.074 mm or less. When the particle size of the fine powder is 0.074 mm or less, the effect of improving the strength due to the densification of the matrix portion is obtained. Examples of the fine powder include alumina-siliceous particles, alumina particles, and siliceous particles. Examples of the alumina-siliceous particles constituting the fine powder include clay, chamotte particles, andalusite particles, and mullite particles.
[0021] Examples of the aluminous particles constituting the fine powder include aluminium shale, bauxite, brown alumina, fused alumina, calcined alumina, etc. Examples of the siliceous particles constituting the fine powder include silica stone, silica fume, etc.
[0022] The unfired alumina-silica brick may further contain other components. Examples of the other components include impurities that are inevitably contained. Examples of the other components include Fe2O3 and the like. Unfired alumina-silica bricks are not fired. "Unfired" means that they are not heated to a temperature exceeding 500°C during production. The porosity of unfired alumina-silica bricks is preferably 10% or more and 18% or less. When the porosity is 10% or more and 18% or less, heat spalling resistance and physical strength sufficient to withstand operation are obtained. The porosity is measured according to JIS R 2205.
[0023] The compressive strength of the unfired alumina-silica brick is preferably 30 MPa or more and 60 MPa or less. When the compressive strength is 30 MPa or more and 60 MPa or less, a mechanical strength sufficient for operation is obtained. In addition, the compressive strength is equivalent to that of general fired alumina bricks. The compressive strength is measured according to JIS R 2206.
[0024] 2. Manufacturing method of unfired alumina-silica bricks In a method for producing unfired alumina-silica bricks, a mixture of particles containing alumina, particles containing silica, and an aqueous phosphate solution is molded, and the molded product is dried at a temperature of 250°C or higher and 500°C or lower.
[0025] Examples of the particles containing alumina include alumina-siliceous particles, alumina particles, etc. Examples of the alumina-siliceous particles include clay, chamotte particles, andalusite particles, mullite particles, etc. Examples of the alumina particles include aluminium shale (bandketgan), bauxite, brown alumina, fused alumina, calcined alumina, etc.
[0026] Examples of the particles containing silica include alumina-siliceous particles, silica particles, etc. Examples of the alumina-siliceous particles include clay, chamotte particles, andalusite particles, mullite particles, etc. Examples of the siliceous particles include silica stone, silica fume, etc.
[0027] Examples of the phosphate contained in the phosphate aqueous solution include aluminum phosphate. The components contained in aluminum phosphate are unlikely to react with components in the brick, such as alumina components. Therefore, aluminum phosphate is unlikely to lower the melting point of the unfired alumina-silica brick, and is unlikely to reduce the corrosion resistance of the unfired alumina-silica brick. The concentration of the phosphate in the phosphate aqueous solution is preferably 30% by mass or more and 50% by mass or less. The phosphate aqueous solution functions, for example, as a binder.
[0028] The alumina-containing particles and silica-containing particles include, for example, coarse particles and medium particles constituting the aggregate, and fine powder constituting the matrix. The aggregate has a particle size of, for example, 0.074 mm or more and 5 mm or less. The fine powder has a particle size of, for example, 0.074 mm or less.
[0029] According to the manufacturing method of the present disclosure, for example, the unfired alumina-silica brick described above in "1. Configuration of unfired alumina-silica brick" can be manufactured. 3. Benefits of Unburned Alumina-Silica Bricks (1A) Unfired alumina-silica bricks have high hydrogen gas resistance.
[0030] (1B) In the unfired alumina-silica brick, for example, the content of P2O5 is from 0.5% by mass to 4% by mass, in which case the hydrogen gas resistance of the unfired alumina-silica brick is even higher. 4. Working Example (4-1) Manufacturing of unburned alumina-silica bricks S1 The following raw materials were mixed to obtain a mixture.
[0031] Alumina-silica particles with a particle size of 0.074 mm to 3 mm: 70 parts by weight Alumina-silica particles with a particle size of 0.074 mm or less, a mixture of alumina particles with a particle size of 0.074 mm or less, and silica particles with a particle size of 0.074 mm or less: 27 parts by mass Aluminum phosphate aqueous solution: 3 parts by weight Next, the kneaded material was molded to obtain a molded product, which was then dried at a temperature of 300° C. The drying time was 24 hours.
[0032] Through the above steps, unfired alumina-silica brick S1 was obtained. Among the raw materials, alumina-silica particles with a particle size of 0.074 mm or more and 3 mm or less became aggregate in the unfired alumina-silica brick S1. Among the raw materials, particles with a particle size of 0.074 mm or less became the matrix part in the unfired alumina-silica brick S1.
[0033] The content of each component contained in the unfired alumina-silica brick S1 was measured. The measurement results are shown in Table 1. In addition, the porosity, bulk specific gravity and compressive strength of the unfired alumina-silica brick S1 were measured. The measurement results are shown in Table 1.
[0034] [Table 1]
[0035] (4-2) Manufacturing of fired alumina-silica brick R1 As a comparative example, a fired alumina siliceous brick R1 was produced by a known method. The composition, porosity, bulk specific gravity and compressive strength of the fired alumina siliceous brick R1 are shown in Table 1. The fired alumina siliceous brick R1 did not contain any phosphate. The fired alumina siliceous brick R1 was also fired.
[0036] (4-3) Evaluation of hydrogen gas resistance An evaluation apparatus 1 shown in FIG. 1 was prepared. The evaluation apparatus 1 was equipped with a reaction tube 3. The reaction tube 3 was a hollow cylindrical member made of alumina. The evaluation apparatus 1 was equipped with a tubular furnace 5. The center part of the reaction tube 3 was housed inside the tubular furnace 5. The evaluation apparatus 1 was equipped with a thermocouple 7. The thermocouple 7 can measure the temperature inside the reaction tube 3.
[0037] Next, an alumina boat 6 was installed inside the reaction tube 3 and at the center in the longitudinal direction of the reaction tube 3, and a plurality of test samples 4 were placed on the alumina boat 6. The test samples 4 were unfired alumina-silica bricks S1 and fired alumina-silica bricks R1. The shape of the test sample 4 was a rectangular parallelepiped. The size of the test sample 4 was 10×10×15 mm.
[0038] Next, the test sample 4 was heated in a reducing atmosphere. The procedure for heating in a reducing atmosphere was as follows. First, nitrogen was supplied to the reaction tube 3. The nitrogen entered the reaction tube 3 from the upstream end 3A of the reaction tube 3, flowed inside the reaction tube 3, and was discharged from the downstream end 3B of the reaction tube 3. The flow rate of the nitrogen was 250 mL / min.
[0039] While nitrogen was being supplied to the reaction tube 3, the temperature inside the reaction tube 3 was raised to 1300° C. using the tubular furnace 5. The temperature inside the reaction tube 3 was maintained at 1300° C. until the heating in the reducing atmosphere was completed.
[0040] After the temperature increase was completed, the supply of nitrogen was stopped, and the atmospheric gas G was supplied to the reaction tube 3. The atmospheric gas G was a gas having a hydrogen concentration of 99% or more. The flow rate of the atmospheric gas G was 250 mL / min. The state in which the atmospheric gas G was supplied to the reaction tube 3 was continued for 8 hours.
[0041] Next, the supply of the atmospheric gas G was stopped, and nitrogen was supplied to the reaction tube 3. The state in which nitrogen was supplied to the reaction tube 3 was continued for 16 hours. Next, the supply of nitrogen was stopped, and the atmospheric gas G was supplied to the reaction tube 3. The flow rate of the atmospheric gas G was 250 mL / min. The state in which the atmospheric gas G was supplied to the reaction tube 3 was continued for 8 hours. With the above steps, heating in a reducing atmosphere was completed.
[0042] Next, the temperature inside the reaction tube 3 was lowered to room temperature, and the test sample 4 was taken out. Next, the mass reduction rate N1, the SiO2 component value index N2, and the P2O5 component value index N3 were calculated for each of the unfired alumina-silica brick S1 and the fired alumina-silica brick R1. These are shown in Table 1.
[0043] The mass reduction rate N1 is expressed by the following formula (1). Formula (1) N1 = ((Wa-Wb) / Wa) x 100 In formula (1), Wa is the mass of the test sample 4 before heating in the atmospheric gas G. Wb is the mass of the test sample 4 after heating in the atmospheric gas G. The smaller the mass reduction rate N1, the higher the hydrogen gas resistance performance.
[0044] The SiO2 component value index N2 is expressed by the following formula (2). Formula (2) N2=(Wd / Wc)×100 In formula (2), Wc is the mass of the SiO2 component in the test sample 4 before heating in the atmospheric gas G. Wd is the mass of the SiO2 component in the test sample 4 after heating in the atmospheric gas G. The larger the SiO2 component value index N2, the higher the hydrogen gas resistance performance.
[0045] The P2O5 component value index N3 is expressed by the following formula (3). Equation (3) N3=(Wf / We)×100 In formula (3), We is the mass of the P2O5 component in the test sample 4 before heating in the atmospheric gas G. Wf is the mass of the P2O5 component in the test sample 4 after heating in the atmospheric gas G.
[0046] The unfired alumina-silica brick S1 had a smaller mass reduction rate N1 and a larger SiO2 component index N2 than the fired alumina-silica brick R1. These evaluation results confirmed that the unfired alumina-silica brick S1 has high hydrogen gas resistance.
[0047] The P2O5 component index N3 was small for unburned alumina-silica brick S1. This suggests that the phosphoric acid component protected the silica component. The mass loss rate N1 for unburned alumina-silica brick S1 was equivalent to the mass loss rate N1 for unburned alumina-silica brick S1 heated to the same temperature in air.
[0048] Furthermore, the porosity, bulk density and compressive strength were measured for each of the unfired alumina-silica brick S1 and the fired alumina-silica brick R1 after heating in the atmospheric gas G. Table 2 shows the porosity, bulk density and compressive strength before and after heating in the atmospheric gas G.
[0049] [Table 2]
[0050] "Before" in Table 2 means before heating in atmospheric gas G. "After" in Table 2 means after heating in atmospheric gas G. For unfired alumina-silica brick S1, the compressive strength after heating in atmospheric gas G was greater than the compressive strength before heating in atmospheric gas G. Although P2O5 was reduced by heating in atmospheric gas G, it is presumed that the SiO2 component formed clay bonds due to the heat received, thereby compensating for the strength.
[0051] On the other hand, in the case of the fired alumina-silica brick R1, the compressive strength after heating in the atmospheric gas G was significantly smaller than the compressive strength before heating in the atmospheric gas G. When heated in the atmospheric gas G, a reaction represented by the following reaction formula (4) occurs. (Formula 4) SiO2(s)+H2(g)→SiO(g)+H2O(g) In the case of the unburned alumina-silica brick S1, the phosphoric acid component forms a film on the surface of the unburned alumina-silica brick S1 to protect the silica component, thereby suppressing the reaction of (Equation 4). As a result, it is presumed that the mass reduction rate N1 is small and the SiO2 component value index N2 is large.
[0052] 5. Other embodiments Although the embodiments of the present disclosure have been described above, the present disclosure is not limited to the above-described embodiments and can be implemented in various modified forms.
[0053] (1) The function of one component in each of the above embodiments may be shared by multiple components, or the functions of multiple components may be performed by one component. Also, part of the configuration of each of the above embodiments may be omitted. Also, at least part of the configuration of each of the above embodiments may be added to or substituted for the configuration of another of the above embodiments.
[0054] (2) In addition to the unfired alumina-silica brick described above, the present disclosure can be realized in various forms, such as a system including the unfired alumina-silica brick as a component, a method for manufacturing a hot stove, and a method for manufacturing a blast furnace shaft. [Explanation of symbols]
[0055] 1...Evaluation device, 3...Reaction tube, 3A...Upstream end, 3B...Downstream end, 4...Test sample, 5...Tubular furnace, 6...Alumina boat, 7...Thermocouple
Claims
1. A 2 O 3 Contains 30% by mass or more and 90% by mass or less, SiO 2 Contains 10% by mass or more and 65% by mass or less, P 2 O 5 Contains 0.5% by mass or more and 4% by mass or less, Unburned alumina-silica bricks for hot stoves or blast furnace shafts.
2. A 2 O 3 Contains 50% by mass or more and 60% by mass or less, SiO 2 Contains 35% by mass or more and 45% by mass or less, P 2 O 5 Contains 0.9% by mass or more and 1.5% by mass or less, Unburned alumina-silica bricks for hot stoves or blast furnace shafts.
3. A kneaded mixture of particles containing alumina, particles containing silica, and an aqueous phosphate solution is molded, Drying the molded product at a temperature of 250°C or higher and 500°C or lower. A method for producing unburned alumina-silica bricks for use in hot stoves or blast furnace shafts.
Citation Information
Patent Citations
Alumina-silica-based brick
JP2017065956A